THE RELATIONSHIP BETWEEN ADDITIONAL TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION AND INCREASING THE EFFECTIVENESS OF PHYSICAL EXERCISE IN REDUCE PAIN IN LOW BACK PAIN - Meigy Nitalessy (Molucca Medica, 2023)
Low back pain (LBP) is a common problem that affects many people around the world. Physical exercise is one of the most commonly used interventions for LBP, but its effectiveness can be limited by pain experienced during exercise. Transcutaneous Electrical Nerve Stimulation (TENS) is a non-invasive technique that has been found to be effective in reducing pain in LBP patients. The aim of this literature review is to investigate the relationship between the addition of TENS to physical exercise and its effectiveness in reducing pain in LBP patients. A comprehensive search of databases was conducted, and studies that met the inclusion criteria were analyzed. The results of this review suggest that the addition of TENS to physical exercise can be effective in reducing pain in LBP patients. TENS can prepare the muscles of the body before exercise, making physical exercise more effective and reducing pain. However, the effectiveness of TENS may be limited to the short-term, and more research is needed to fully understand the long-term effects of TENS as an adjunct for physical exercise. Furthermore, the optimal dosage, duration, and frequency of TENS use in combination with physical exercise for LBP patients remains to be determined. Overall, the addition of TENS to physical exercise can be a useful adjunct in reducing pain in LBP patients, but more research is needed to fully understand its potential benefits and limitations.